Retorno à atividade desportiva após artroplastia unicompartimental do joelho: uma revisão sistemática da literatura - Maurício Daniel Teixeira Dias (2022)
Objective: Over the years, the unicompartmental knee arthroplasty has been used more frequently, becoming an important treatment of degenerative knee disease, also in younger patients with higher post-surgical expectations, being the return to sports one of the most sought-after goals. Thus, the goal of this systematic review is to quantify the return to sports after surgery, as well as characterize the sport in terms of impact level. Material and Methods: Using the data bases of PubMed, the Cochrane Library, Web of Science and Scopus, a search was made for articles published between 2015 and 2022, with no language restriction, that would quantify the number of patients who, after unicompartmental knee arthroplasty, would return to sports and would identify the sport that was resumed, as well as the impact level. Results: Starting with a total of 37 articles, 5 were included, of which 4 were case series and 1 was a cohort, with a total of 277 patients who underwent a unicompartmental knee arthroplasty. The return to sports was high, varying from 86% to values higher than 100%. As to the level of impact of the sport, to notice a change from high-impact to low-impact sports. Conclusion: The results of this systematic review demonstrate that using a unicompartmental knee arthroplasty is efficient in treating knee osteoarthritis in patients who aim to return to sports after the surgery, as well as showing a preference for low-impact sports after the surgery.